1H, 13C, and 15N resonance assignment of the N-terminal domain of Mason-Pfizer monkey virus capsid protein, CA 1-140 - Macek, Pavel; Zídek, Lukás; Rumlová, Michaela; Pichová, Iva; Sklenár, Vladimír (Biomolecular NMR assignments, 2008)
Mason-Pfizer monkey virus (M-PMV) belongs to the family of betaretroviruses characterized by the assembly of immature particles within cytoplasm of infected cells in contrast to other retroviruses (e.g. HIV, RSV) that assemble their immature particles at a plasma membrane. Simultaneously with or shortly after budding a virus-encoded protease is activated and the Gag polyprotein is cleaved into three major structural proteins: matrix (MA), capsid (CA), and nucleocapsid (NC) protein. Mature retroviral CA proteins consist of two independently folded structural domains: N-terminal domain (NTD) and C-terminal dimerization domain (CTD), separated by a flexible linker. As a first step toward the solution structure elucidation, we present nearly complete backbone and side-chain 1H, 13C and 15N resonance assignment of the M-PMV NTD CA.
Keywords: protony; izotopy uhlíku; Protein Structure, Tertiary; Nitrogen Isotopes; sekvence aminokyselin; Capsid Proteins; terciární struktura proteinů; Carbon Isotopes; Molecular Sequence Data; Amino Acid Sequence; magnetická rezonanční spektroskopie; molekulární sekvence - údaje; molekulová hmotnost; Mason-Pfizer monkey virus; Masonův-Pfizerův opičí virus; virové plášťové proteiny; izotopy dusíku; Protons; Magnetic Resonance Spectroscopy; Molecular Weight